X-(9x-10)+11=12x+3(-2x+.33

Simple and best practice solution for X-(9x-10)+11=12x+3(-2x+.33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-(9x-10)+11=12x+3(-2x+.33 equation:



X-(9X-10)+11=12X+3(-2X+.33
We move all terms to the left:
X-(9X-10)+11-(12X+3(-2X+.33)=0
We add all the numbers together, and all the variables
X-(9X-10)-(12X+3(-2X+0.33)+11=0
We get rid of parentheses
X-9X-(12X+3(-2X+0.33)+11+10=0
We add all the numbers together, and all the variables
-8X-(12X+3(-2X+0.33)+11+10=0

See similar equations:

| -14x^+6x^2-12=0 | | 3n+11=29 | | 3=c-5 | | 2=-m/4 | | 440/x-25+201=286 | | 3x²+3x-72=0 | | 6r^2-2r-40=4r^2 | | 2/3(9s-3/2)=s(0.45+5)+1.2. | | 4x²+9x+8=x²-6x+80 | | s=3+1/2s+20=74 | | 30•r=57 | | 2x+4=3x-6(x=4) | | x/27=-11/27 | | -87=-7+4(4+4p)A-13 | | 14=13x-5-12x | | 3,4-0,6x=2x-(0.4+1) | | a^-4a=5 | | 2x-1/3=x+3 | | 14=13x-5-13x | | -3x+10=0 | | 5x-9-3x=3x-4 | | x-437=329 | | p^2+2=-5-8p | | 0.05x=-44,500 | | n^2+4n=2n | | -(2x)=0 | | 2=​2​​m​​− | | 5x+2(3x-3)=49 | | 12+7s=8s | | 3.4=-13.6=(-3.4c)+1.7c | | x–69.80=36.24 | | -3r^2-r-6=-4r^2 |

Equations solver categories